Capsular Genotyping of Methicillin-Resistant Staphylococcus aureus (MRSA) from Human and Animal Sources Using Duplex PCR - Khandelwal, Shivali; Bhati, Taruna; Yadav, Vishal; Kumar, Sudesh; Dhruw, Reshma; Shringi, Brij Nandan (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Capsular polysaccharides, particularly types 5 and 8 encoded by the cap5K and cap8K genes, are key virulence factors in Staphylococcus  aureus, contributing to immune evasion through resistance to phagocytosis. This study aimed to determine the prevalence and  distribution of these capsule-associated genes among 78 methicillin-resistant S. aureus (MRSA) isolates obtained from various human  and animal sources in Western India. Duplex PCR targeting cap5K and cap8K was employed for genotypic characterization. Among the  isolates, 75 (96.15%) were typeable, while 3 (3.85%) were non-typeable (NT). The cap5K genotype was the most prevalent (44.87%),  followed by cap8K (26.92%), and dual gene presence was 24.36%. Notably, dual gene carriage was more common in human isolates  (50.00%), whereas cap5K alone predominated in animal isolates, particularly in unprocessed meat (60.00%) and animal pus (48.00%).  The NT strains were exclusively identified in animal pus samples. A Chi-square test revealed a statistically significant association between  sample type and capsule gene distribution (χ² = 17.87, p = 0.037). These findings highlight the dominance of cap5K in this region and  the influence of host source on capsule gene variation, underlining the importance of ongoing molecular surveillance to understand  the epidemiological and pathogenic dynamics of MRSA.
Keywords: cap5K, cap8K, Capsular polysaccharide, Duplex PCR, MRSA, Staphylococcus aureus.